2010
DOI: 10.1111/j.1937-5956.2009.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Delayed Incentives on Supply Chain Profits and Consumer Surplus

Abstract: We examine the use of consumer cash mail‐in rebates offered by a manufacturer in a Stackelberg game where the manufacturer is the leader and the retailer is the follower. Our analysis indicates that rebates are profitable for manufacturers if consumers are inconsistent in the sense that their rebate valuation when they make purchase decisions is independent of their redemption probabilities when they make redemption decisions. If the manufacturer keeps the wholesale price unchanged, then the rebate increases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 40 publications
1
29
0
1
Order By: Relevance
“…() showed that due to slippage, manufacturer rebates can always enhance the manufacturer's profit. Along similar lines, Khouja and Zhou () found that rebates are only profitable if consumers are inconsistent in their decision to purchase and their decision to redeem. Therefore, incorporating both hassle cost and slippage in our model is important.…”
Section: Introductionmentioning
confidence: 82%
“…() showed that due to slippage, manufacturer rebates can always enhance the manufacturer's profit. Along similar lines, Khouja and Zhou () found that rebates are only profitable if consumers are inconsistent in their decision to purchase and their decision to redeem. Therefore, incorporating both hassle cost and slippage in our model is important.…”
Section: Introductionmentioning
confidence: 82%
“…Nalla et al (2008) design a combined rebate mechanism (a retailer-sponsored rebate together with a manufacturer-sponsored wholesale price rebate) to coordinate the supply chain. Khouja and Zhou (2010) show that an incentive contract in which the manufacturer's rebate value is negatively linked with the retailer's price can improve the performance of a decentralized supply chain. Saha (2013) studies several different rebated-induced contracts under a deterministic demand setting, and for simplicity the model assumes no slippage behaviour.…”
Section: Relevant Literaturementioning
confidence: 99%
“…For instance, Yang et al (2010) study how manufacturer-suggested retail prices (MSRP) interact with rebates. In a similar vein, Khouja and Zhou (2010) study a supply chain where the manufacturer implements incentives that curb the retail price. They use a model where consumers are heterogeneous in the value they derive from a rebate.…”
Section: Literature Reviewmentioning
confidence: 99%